Główne założenia projektów ustaw o odpowiedzialności nieletnich na gruncie prawa karnego, opracowanych w początkach II Rzeczypospolitej - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper is devoted to the main principles of draft legislation concerning juvenile liability under criminal law formulated in the early days of the Second Polish Republic. The author discusses the most important legal terms and constructs of the drafts formulated by Józef Reinhold and the Codification Commission of the Republic of Poland.He demonstrates that juvenile liability under criminal law was presented in a concise and clear manner in the draft regulations, with the legislators reaching a compromise over the latest views of the proponents of the legal doctrine at the time and making a creative use of the solutions used in other countries as well as these countries’ experiences. The aim of the Polish proposals was, first of all, to reform the juvenile offenders and not to put them in prison. The reform of criminal law applying to juveniles was meant to formulate special legal regulations as well as an autonomous adjudication procedure. It should be emphasised that the suggestions formulated in the Polish legal doctrine and legislation in the inter-war period were taken into account in the Polish Criminal Code of 1932 and still constitute the basis for dealing with juveniles committing criminal offences.
Keywords: odpowiedzialność nieletnich; II Rzeczpospolita; Komisja Kodyfikacyjna Rzeczypospolitej Polskiej 1919-1939